2017
DOI: 10.1039/c6ew00270f
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazole (BT) and BT plant metabolites in crops irrigated with recycled water

Abstract: Novel benzotriazole plant metabolites were quantified for the first time in crops irrigated with recycled water, demonstrating an exposure route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 72 publications
3
40
0
Order By: Relevance
“…Biofilter mesocosms are exposed to three storm events with seven days of treatment time in between and then monitored for an additional 21 days. This study hypothesizes that vegetation will improve biofilter mesocosm performance and that BT will be taken up by C. praegracilis and metabolized yielding similar metabolites as observed previously [33,40]. This study demonstrates that significant masses of BT and BT metabolites were observed in C. praegracilis and that a substantial missing sink of BT developed in the vegetated biofilters after the conclusion of the storm events.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Biofilter mesocosms are exposed to three storm events with seven days of treatment time in between and then monitored for an additional 21 days. This study hypothesizes that vegetation will improve biofilter mesocosm performance and that BT will be taken up by C. praegracilis and metabolized yielding similar metabolites as observed previously [33,40]. This study demonstrates that significant masses of BT and BT metabolites were observed in C. praegracilis and that a substantial missing sink of BT developed in the vegetated biofilters after the conclusion of the storm events.…”
Section: Introductionsupporting
confidence: 77%
“…BT and GBT were detected in the both C. praegracilis leaf and root tissue in the control biofilters (Figure 6a-d), indicating that BT is able to accumulate in C. praegracilis even at low background concentrations. The detection of BT is most likely due to the exposure of the control biofilter mesocosms to BT spiked stormwater during the preliminary tests (Appendix B) as well as continued exposure from low ambient concentrations in the tap water [33,40]. This indicates that BT is able to accumulate in C. praegracilis, even at low background concentrations, and that BT and GBT are able to persist in vegetation for extended periods of time.…”
Section: Bt and Bt Metabolitesmentioning
confidence: 98%
“…It has been suggested that duckweeds may remove BZT from water (Gatidou et al., ), and other plants are already known to metabolize BZT (e.g., LeFevre et al., , ). We saw stronger decreases in BZT when salt was absent, which could be due to enhanced plant growth and therefore greater biotransformation, or the reverse: greater biotransformation at low salt facilitated enhanced duckweed growth and survival (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that 17 -estradiol, sulfamethoxazole, sulfadiazine, estrone, triclosan, acetaminophen, caffeine, carbadox and lamotrigine were extensively metabolized in the radish plants with the mass recoveries ranging from 3.0 to 32.1% after 7 days of hydroponic exposure (Li et al, 2018). In some cases, the amount of formed metabolites can even be greater than the accumulated parent compounds (Goldstein et al, 2014;LeFevre et al, 2017;LeFevre et al, 2015;Macherius et al, 2012a;Malchi et al, 2014;Riemenschneider et al, 2017). For example, Macherius et al (2012a) reported that the total amount of eight phase-II triclosan conjugates was about 5 times that of triclosan in carrot roots after twomonth growth in soil.…”
Section: Plant Uptakementioning
confidence: 99%